Analisis Dan Usulan Perbaikan Pencahayaan Pada Ruang Skripsi Perpustakaan Pusat Universitas Sebelas Maret Surakarta - Bambang Suhardi; Pringgo Widyo Laksono; Raqibanul Hakim (Performa: Media Ilmiah Teknik Industri, 2015)
Library with good environment will create comfort, calmness, and satisfaction for users while doing the activities. One of the aspects to consider in creating a good library environment is lighting. Lighting needs can be met from day lighting and artificial lighting. Artificial lighting had advantage in terms of relatively constant light intensity in the range of work hours, but this approach requires electric operating costs. This research analyzes the current lighting conditions in Sebelas Maret University library that influenced by day lighting and artificial lighting. The analysis process will be using software surfer V.10 based on the value of the intensity of light at each measuring point. The result indicated that the average of light intensity is still below the prescribed standard so that redesign needs to be done. In the redesign process only focuses on the artificial lighting that calculated using lumen method with two different conditions.